Aesthetic treatment of molar-incisor hypomineralization lesions in a pediatric patient. - Aguilera - Flores , A.; Guzmán de Hoyos , A.I.; Díaz - Palomares , E.; Hernández - Castillo , E.I.; Meléndez - Wong , C.A (Revista de Ciencias Médicas Torreón, 2026)
Molar-incisor hypomineralization (MIH) is a qualitativeenamel defect affecting the first permanent molars and,frequently, the incisors as well. It manifests as opaque white,cream, or yellowish-brown areas associated with sensitivity,post-eruptive fractures, and an increased risk of caries. Itsorigin is linked to a defect in enamel maturation during thefirst three years of life, although the exact causes remainunder investigation. The etiology of MIH is multifactorial,involving systemic factors—such as febrile illnesses,respiratory infections, prolonged antibiotic use, and perinatalcomplications—that can interfere with ameloblast functionduring tooth development. Global prevalence ranges fromEl aislamiento absoluto se efectuó con dique de goma, clampindividualysellado periférico con sellador líquido,libre degarantizando un campo operatorio secoycontaminación. Se efectuó profilaxis inicial con piedrapómez y cepillo de goma sin flúor.Tratamiento en dientes anteriores.Se empleó un protocolo combinado de microabrasión einfiltración resinosa (ICON®).15% to 40.2%, depending on the country and diagnosticcriteria; in Mexico, the most robust studies place theprevalence between 13.9% and 15.8%, although one specificstudy suggests a figure as high as 30.9%, and the condition isrecognized as a growing public health issue.1.- Microabrasión:Aplicación de base ácida (Antivet, HCl 21% estabilizado, pH3) durante 1–5 minutos, seguida de enjuague.Aplicación de base alcalina (hidróxido de calcio, pH >12) por